PENGEMBANGAN GAME MEMASAK KULINER TRADISIONAL KHAS PATI “ GaGe Go” MENGGUNAKAN CONSTRUCT 2 - Indriani, Indriani; Wibisono, Setyawan (Information Technology and Telematics, 2018)
Abstract - Today the development of information technology and games among children to adulthood is very rapid, so the game not only as entertainment to play, but now the game can train the power of thought and logic. Adventure education game to save Javanese script is a game created using collision detection method, by doing collision detection process between objects in game, collision detection is very important in making this game and if collision detection is not applied, then the game is not working properly. This study aims to produce the design of educational games let learn Javanese script, and develop games that can provide entertainment as well as learning mediatraditional culinary pati “ ga ge go” using construct 2.